নির্বাচিত বেগম : অর্ধশতাব্দীর সমাজচিত্র, ১৯৪৭-২০০০, প্রথম খণ্ড - বেগম, মালেকা
Contributed articles on socioeconomic conditions of women in Bangladesh and erstwhile East Bengal; selections from various issues published between 1947 and 2000 of 'Begama' journal on women's issues published from Bangladesh.